1998
DOI: 10.1007/s002200050297
|View full text |Cite
|
Sign up to set email alerts
|

Extensions of Conformal Nets¶and Superselection Structures

Abstract: Starting with a conformal Quantum Field Theory on the real line, we show that the dual net is still conformal with respect to a new representation of the Möbius group. We infer from this that every conformal net is normal and conormal, namely the local von Neumann algebra associated with an interval coincides with its double relative commutant inside the local von Neumann algebra associated with any larger interval. The net and the dual net give together rise to an infinite dimensional symmetry group, of which… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
145
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(145 citation statements)
references
References 31 publications
0
145
0
Order By: Relevance
“…In [12] it was shown that a unitary representation of the Möbius group Möb is generated by the modular groups of a "halfsided modular triple", i.e., three von Neumann algebras A i (i = 0, 1, 2) with a joint cyclic and separating vector Ψ such that if σ i t is the modular group for (A i , Ψ ), then σ i t (A i+1 ) ⊂ A i+1 for t 0. (Here, i + 1 is understood mod 3.)…”
Section: A Modular Construction Of Möb × Möb In the Split Statementioning
confidence: 99%
“…In [12] it was shown that a unitary representation of the Möbius group Möb is generated by the modular groups of a "halfsided modular triple", i.e., three von Neumann algebras A i (i = 0, 1, 2) with a joint cyclic and separating vector Ψ such that if σ i t is the modular group for (A i , Ψ ), then σ i t (A i+1 ) ⊂ A i+1 for t 0. (Here, i + 1 is understood mod 3.)…”
Section: A Modular Construction Of Möb × Möb In the Split Statementioning
confidence: 99%
“…Finally if d(c) = 1 then, for every I ∈ I, π (λ,q) (A (Vir,c) (I)) = A U(1) (I) which is impossible since A U(1) is strongly additive (see [5,26]) while A (Vir,c) it is not. Now let G be a simply connected compact Lie group with simple Lie algebra Lie(G) and let k be a positive integer.…”
Section: Theorem 35 a Local Extension B Of A (Vir1) Is Of Compact mentioning
confidence: 99%
“…All these properties are indeed "additional": there are Möbius covariant nets which are not even 3-regular (see the examples in [12]). …”
Section: Möbius Covariant Netsmentioning
confidence: 99%
“…The latter class (see Sect. 2 for the definition) includes every strongly additive diffeomorphism covariant net on S 1 and hence every diffeomorphism covariant net which is completely rational in the sense of [18], the nets generated by chiral current algebras [1,12,27,30] and their orbifold subnets [31]. Since the Möbius symmetry of a given net on S 1 is completely determined by the vacuum vector [9,Theorem 2.19] our result shows that in the above cases the Diff + (S 1 ) symmetry of the net is also determined by this vector.…”
Section: Introductionmentioning
confidence: 99%